A New Biomarker Tool for Risk Stratification in “de novo” Acute Heart Failure (OROME) - Agra-Bermejo, Rosa M.; Cacho-Antonio, Carla; Gonzalez-Babarro, Eva; Rozados-Luis, Adriana; Couselo-Seijas, Marinela; Gómez-Otero, Inés; Varela-Román, Alfonso; López-Canoa, José N; Gómez-Rodríguez, Isabel; Pata, María; Eiras, Sonia; González-Juanatey, Jose R. (Frontiers in Physiology, 2022)
Background: Inflammation is one of the mechanisms involved on heart failure (HF) pathophysiology. Thus, the acute phase reactant protein, orosomucoid, was associated with a worse post-discharge prognosis in de novo acute HF (AHF). However, the presence of anti-inflammatory adipokine, omentin, might protect and reduce the severity of the disease. We wanted to evaluate the value of omentin and orosomucoid combination for stratifying risk of these patients. Methods and Results: Two independent cohorts of patients admitted for de novo AHF in two centers were included in the study (n=218). Orosomucoid and omentin circulating levels were determined by ELISA at discharge. Patients were follow-up for 317 (3-575) days. A predictive model was determined for primary endpoint, death and/or HF readmission. Differences in survival were evaluated using a Log-rank test. According cut-off values of orosomucoid and omentin, patients were classified on UpDown (high orosomucoid and low omentin levels), equal (both proteins high or low) and DownUp (low orosomucoid and high omentin levels). The Kaplan Meier determined worse prognosis for the UpDown group (Long-rank test p=0.02). The predictive model that includes the combination of orosomucoid and omentin groups (OROME) + NT-proBNP values achieved a higher C-index=0.84 than the predictive model with NT-proBNP (C-index=0.80) or OROME (C-index=0.79) or orosomucoid alone (C-index=0.80). Conclusions: The orosomucoid and omentin determination stratifies de novo AHF patients in high, mild and low risk of rehospitalization and/or death for HF. Its combination with NT-proBNP improves its predictive value in this group of patients. KEYWORDS; Inflammation markers, adipokine markers, acute de novo heart failure